Faith in Fate: Plot, Gods, and Metapoetic Morality in Valerius Flaccus - Lovatt, Helen (University of Toronto Press, 2018)
This paper examines fides as a literary concept and asks how metaliterary faith fits in with morality, intertextuality and trust in the gods. It begins by examining the phrase nec vana fides in situations related to prophecy and belief in the gods, including the prophetic contest of Mopsus and Idmon, and Valerius’ invocation of Bacchus at Callirhoe. The second section explores ideas of faith at Lemnos, used by Venus and in Hypsipyle’s tour of Lemnos’ divine landscape. The rhetoric of faith often accompanies deception. Faith is also used to reflect on the difficulties of working with (and living in) a traditional narrative: gods who cannot change the outcome of the story, and men whose trust in gods (and themselves) is misplaced. The section on the helmsman also investigates the connection between faith and narrative. The second half of the article focuses mainly on Jason and Medea, examining Jason’s use of the rhetoric of faith and trust, and Medea’s metaliterary trust in and rejection of her own past (literary and familial), in her negotiations with Aeetes, the dragon scene, the marriage scene and the final quarrel between Jason and Medea. This first examination of the language of metaliterary faith in Valerius Flaccus sets out an important nexus of ideas about intertextuality, authority, myth and power that is extendable not just to other Latin epics but also the use of fides in other mythological genres. The particular prominence of this language in Valerius’ Flavian Argonautica suggests that belatedness and political anxieties combine to make metaliterary fides a peculiar concern of Flavian epic.